2019
DOI: 10.1007/s11884-019-00519-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Stress Incontinence in Women

Abstract: Purpose of Review This review aims to discuss the current literature addressing associations between physical activity and stress urinary incontinence in women. Recent Findings Multiple cross-sectional studies utilize survey questionnaires to determine prevalence of stress urinary incontinence, impact of various types and intensities of physical activity on stress urinary incontinence, and explain differences in urinary symptoms among active women. Summary Although there is evidence for increased rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
(93 reference statements)
0
14
0
5
Order By: Relevance
“…We purposely aimed to recruit a typical sample of beginner exercisers at fitness clubs, and our participants are therefore more diverse than those of previous studies with respect to age, BMI, and parous and nulliparous women [8,22]. Mean age was about 35 years and nearly 40% had a BMI ≥ 25 and as such were classified as overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We purposely aimed to recruit a typical sample of beginner exercisers at fitness clubs, and our participants are therefore more diverse than those of previous studies with respect to age, BMI, and parous and nulliparous women [8,22]. Mean age was about 35 years and nearly 40% had a BMI ≥ 25 and as such were classified as overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that PFMT is also a key component for prevention of UI [8]. Therefore, in light of this and that UI affects exercisers at higher rates than inactive women [8,22], PFMT should probably be incorporated into popular group exercise classes and training programs for women at fitness clubs. Also, with respect to the social stigma around UI, and because many women are hesitant to talk about their symptoms because of embarrassment [22], a more population-based strategy for inclusion of PFMT would undoubtedly be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has several benefits for the body, and women should not be discouraged from remaining active. Adding exercise as a part of lifestyle helps prevent non-communicable diseases such as diabetes mellitus, hypertension, hypercholesterolemia, and obesity [46]. An RCT done by Said et al (2017) randomly divided 32 obese women into high-impact aerobics groups and low-impact aerobics combined with a strength training program group [47].…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%
“…According to Abrams et al, it is clear that high impact exercise leads to stress UI, with a dose-dependent deleterious effect, while low-impact sports might be protective [ 2 ]. In a review of 36 publications addressing the associations between physical activity and SUI, Chisholm et al found evidence for increased rates of SUI among women who are physically active [ 3 ]. In a study quantifying SUI in 104 young female athletes, 52% of the participants self-reported SUI according to the ICQ_UI_SF score [ 4 ].…”
Section: Introductionmentioning
confidence: 99%